The Etiology of Upper Extremity Amputation in Lower Punjab Pakistan - Khan, Muhammad Kamran; Israr, HM; Shah, Wisal; Uzma, Bibi (Poltekkes Kemenkes Jakarta I, 2024)
Background: Amputation, a common orthopedic procedure, is often necessary due to severe trauma or vascular diseases, yet it can lead to psychological issues. This study investigates the causes of upper limb amputation in a specific region of Pakistan to raise awareness and mitigate risks. Aims: To identify causes of upper limb amputation in a specific region of Pakistan and raise awareness to prevent such occurrences. Methods: A cross-sectional study was conducted on upper limb amputations in South Punjab between January 2015 and June 2017. Data from 1174 patients, collected at the Physical Rehabilitation Centre in Muzaffargarh, were analyzed based on age, gender, amputation level, and affected side using HMIS, PMRN, and Microsoft Excel. Results: Analysis revealed a male-to-female ratio of 824:350, with the highest incidence among individuals aged 31 to 45. Crush injuries, primarily caused by the